2022
DOI: 10.1128/mra.00816-22
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of the Tomato Stem Endophyte Bacillus safensis TS3

Abstract: Tomato stem endophyte Bacillus safensis TS3 was isolated from surface-sterilized stems of greenhouse tomato plants. Here, we sequenced the complete genome of this strain to understand the molecular mechanisms underlying its beneficial activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Recently, the genome of the strain TS3 Bacillus safensis was sequenced [ 39 ]. It has been shown that more than 6% of the TS3 genome is associated with the production of various metabolites capable of stimulating plant growth and relieving abiotic stresses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the genome of the strain TS3 Bacillus safensis was sequenced [ 39 ]. It has been shown that more than 6% of the TS3 genome is associated with the production of various metabolites capable of stimulating plant growth and relieving abiotic stresses.…”
Section: Resultsmentioning
confidence: 99%
“…Genome analysis was carried out as described in [ 39 ]. Genome annotation was performed using the NCBI Prokaryotic Genome Annotation Pipeline (PGAP-6.1) [ 90 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation